2020
DOI: 10.1136/gutjnl-2019-320027
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of hepatitis delta virus infection in Cameroon

Abstract: ObjectiveTo investigate the distribution and risk factors of hepatitis delta virus (HDV) infection in Cameroon.DesignWe tested for hepatitis B virus (HBV) surface antigen (HBsAg) and anti-HDV antibody 14 150 samples collected during a survey whose participants were representative of the Cameroonian adult population. The samples had already been tested for hepatitis C virus and HIV antibodies.ResultsOverall, 1621/14 150 (weighted prevalence=11.9%) participants were HBsAg positive, among whom 224/1621 (10.6%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…1A). HDV seroprevalence in Cameroon was 10.6% in 1,621 unselected HBsAg-positive individuals in 2011 68 and 46.7% in 1,928 HBsAg-positive hospital patients in 2010 to 2016, 69 while it was 27.7% in 303 HBsAg carriers between 2005 and 2008 in Gabon. 70 In both countries there were large regional variations.…”
Section: Key Pointmentioning
confidence: 92%
“…1A). HDV seroprevalence in Cameroon was 10.6% in 1,621 unselected HBsAg-positive individuals in 2011 68 and 46.7% in 1,928 HBsAg-positive hospital patients in 2010 to 2016, 69 while it was 27.7% in 303 HBsAg carriers between 2005 and 2008 in Gabon. 70 In both countries there were large regional variations.…”
Section: Key Pointmentioning
confidence: 92%
“…Except the ubiquituous genotype 1 (HDV-1), each virus clade has its distinct geographic distribution: HDV-2 is found in Japan, Taiwan, and Russia; HDV-4 in Taiwan and Japan; HDV-3 in the Amazone bassin; and HDV-5, HDV-6, HDV-7 and HDV-8 in Africa [3,4] . In a recent large representative sample of the adult population of Cameroon, we found an extreme degree of heterogeneity of HDV distribution across Cameroon, ranging from 1% to 54% according to regions, with the highest prevalence found in the Southern and Eastern regions close to the Equator [5] . A single study conducted about three decades ago on HDV infection among Baka Pygmies in Cameroon reported a very high antibody prevalence of 46%, but HDV genetic diversity has not been studied in this population [6].…”
Section: Textmentioning
confidence: 75%
“…Among people positive for hepatitis B surface antigen (HBsAg), preliminary population attributable fraction estimates of HDV were 18% for those with cirrhosis and 20% for those with hepatocellular carcinoma (HCC) 22 . In an epidemiological study in Cameroon, evidence was found for substantial intra-household transmission of HDV as well as large differences in prevalence between regions, the reasons for which remain unclear 23 . The epidemiology of HDV infection has been overlooked for many years and data are now emerging from different parts of the world that will be instrumental to implement the best policies to control this infectious disease.…”
Section: Jvlmentioning
confidence: 99%